2011 Triennial Surveillance Review : Health Check and Statistical Information. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper (a) provides a snapshot of the overall value added of Fund's surveillance perceived by stakeholders; (b) details where the Fund stands in terms of four operational priorities set out in the 2008 TSR; (c) examines key issues identified in the recent IEO paper on the IMF performance in the run up to the global crisis; and (d) discusses stakeholders' perception on the communication aspects of surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet